Subriemannovské geometrie - Musilová, Pavla, 1976-; Slovák, Jan, 1960-; Masarykova univerzita. Ústav matematiky a statistiky (2019)
V práci shrnujeme základní poznatky o subriemannovských varietách a subriemannovských geodetikách z hlediska různých přístupů. Popisujeme teorii neholonomních riemannovských variet, neholonomních konexí a hledání neholonomních geodetik. Uvádíme do souvislosti přístup neholonomní mechaniky a subriemannovské geometrie a ilustrujeme na konkrétních příkladech.
In this thesis we recall basics about subriemannian structures and subriemannian geodesics from the different points of view. We subscribe the theory of nonholonomic Riemannian structures, nonholonomic connections and nonholonomic geodesics. We are interested in comparison of nonholonomic mechanics and subriemannian geometry in examples.
Vedoucí práce: Jan Slovák
Diplomová práce (Mgr.)--Masarykova univerzita, Přírodovědecká fakulta, 2019
Keywords: Riemannova geometrie; Riemannovy variety; Riemannian geometry; Riemannian manifolds; diplomové práce; master's theses